Leaf anatomical changes in peanut plants in relation to drought stress with or without paclobutrazol and ABA - Karthishwaran, R. Somasundaram, B. Sankar, K. (Journal of Phytology, 2016)
Peanut (Arachis hypogaea L. TVM-2) was grown in field under drought stress in comination with paclobutrazol (PBZ) and abscisic acid (ABA) in order to study their individual and combined effects on leaf anatomical characteristics. The thickness of the leaf, upper and lower epidermis and the number of cells per unit area in the palisade and spongy regions were very much reduced under drought stress. The palisade and spongy layers of mesophylls were well differentiated and the cells are wider and longer as compared to shorter palisade and spongy parenchyma of control. The number of palisade and spongy cells increased per unit area with all treatments as compared with drought stressed and unstressed plants. The vascular bundles of the paclobutrazol treated plants were narrow and dense when compared to control. The xylem vessels of PBZ and ABA treated leaves were much narrow when compared to control plants. Among the treatments the present findings revealed that the growth regulator treatments to the drought stressed plants have great impact on the anatomy of Arachis hypogaea plants.